Hungarian Monitoring, 24 June 1990 . [Magyar rádiófigyelő], 1990. június 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Moldavia decides in favor of independence - Debates over where the unified German capital should be - Increasingly bitter domestic political fights in Poland Domestic Affairs: - Hungarian-Austrian talks on the joint World Exposition - András Sütő on the disturbances in Bucharest - The Democratic Alliance of Hungarians in Romania (RMDSZ) criticizes Iliescu - Norwegian Foreign Minister arrives in Budapest Külpolitika: - Moldávia a függetlenség mellett döntött - Vita az egységes Németország fővárosáról - Egyre elkeseredettebb belpolitikai harc Lengyelországban Belpolitika: - Magyar-osztrák tárgyalások a közös világkiállításról - Sütő András a bukaresti zavargásokról - Az RMDSZ bírálja Iliescut - Budapestre érkezett a norvég külügyminiszter